Implementasi Nilai Pendidikan Agama Islam dalam Menangani Perilaku Temper Tantrum Pada Anak - Habibah, Nur Faiz (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
The limitations of children in conveying their wishes are one of the things that causes temper tantrums. The family environment becomes the place for children's temper tantrum interactions. Temper tantrums cannot occur if the child is alone, temper tantrums occur because of interactions. This study aims to explain the implementation of Islamic religious education in handling temper tantrums in children. In this study, the qualitative approach was used, with locations in Purworejo Hamlet, Kalipait Village, Tegaldlımo District, Banyuwangi Regency. To collect data, the observation method and document analysis were used. In testing the validity of the data, it was measured using the triangulation technique of sources and techniques. Data analysis was carried out by the steps of data reduction, data presentation, conclusions and data verification. Parents give Kasıh love, attention and also Islamic religious education for their children, and this is done repeatedly every day. The implementation of Islamicreligious education taught by parents to children has the effect of reducing the child's temper tantrum significantly. Children slowly understand their responsibilities, abilities and children also feel good love and enough attention from parents and the environment. The result of the implementation of Islamic religious education applied to children in handling temper tantrum behavior in children is experiencing a decrease in temper tantrums committed by children.